Pengaruh Good Corporate Governance, Corporate Social Responsibilty dan Ukuran Perusahaan terhadap Nilai Perusahaan - M. Rafly Akbar Salim; Eni Wuryani (Universitas Muhammadiyah Enrekang, 2023)
The purpose of this study is to examine the effect of Good Corporate Governance, Corporate Social Responsibility, and Company Size on Corporate Value. The testing population is the company that is the lattest in its participation in the Good Governance Perception Index (CGPI) assessment conducted by The Indonesian Institute for Corporate Governance (IICG) from 2020 to 2021 consistently. Using the purposive sampling method, 29 companies were obtained as research samples. The analysis used was regression analysis with SPSS version 22. The results showed that Good Corporate Governance and Corporate Social Responsibility did not have a positive effect on the Company's Value also the Company Size variable has a positive effect on Company Value.